LINGUISTIC AND SOCIOLOGICAL CHARACTERISTICS OF THE LANGUAGE - Rakhimov Sarvarjon (Galaxy International Interdisciplinary Research Journal, 2022)
This article talks about the relationship between language and culture, language and thinking, and the linguistic and cultural importance of language.